Biomarkers for patients with Wilms tumor: a review - Zheng, Hongfeng; Liu, Jiangui; Pan, Xiuwu; Cui, Xingang (Frontiers in Oncology, 2023)
Wilms tumor, originating from aberrant fetal nephrogenesis, is the most common renal malignancy of childhood. The overall survival of WT children is about 90%. Although the existing risk-stratification systems are helpful in identifying patients with poor prognosis, the recurrence rate of Wilms tumor remains as high as 15%. To resolve this clinical problem, diverse studies about occurrence and progression of the disease have been carried out and the results are encouraging. With the further study for mechanism of tumorigenesis, a series of molecular biomarkers have been revealed. Some of them show prognostic value and have been introduced into clinical practice. Identification of these biomarkers can be a supplement to the existing risk-stratification systems. In the future, more biomarkers are sure to be discovered and more studies are required to validate their roles in improving the detection rate of occurrence or recurrence of Wilms tumor and enhancing the clinical outcomes.